ANALISA PERENCANAAN PONDASI BORE PILE SUTET 150 KV TANJUNG BALAI KISARAN - Sudarwati; Christofer Casanova Goldstar Panjaitan (JURNAL TEKNIK SIPIL-ARSITEKTUR, 2019)
Meeting the needs of electricity in today's life is very high. To meet the electricity needs of the PLN community requires a network that is able to reach all areas that require electricity. The PLN network is in the form of an Extra High Voltage Air Line (SUTET) tower by PLN. In writing this final project, I will analyze the bore pile foundation planning for the 150 kv SUTET tower building work Tanjung Balai Kisaran.The research methodology used includes: literature study, data collection in the form of soil data, technical data and top structure data. The data is used to perform calculations and redesign of the foundation so that it will produce the carrying capacity of single piles and groups and finally can determine the reinforcement for pile cap and pedestal foundation.The calculation result of the calculation of the weight of the pile cap / pad, pedestal and soil above the pad is = 30,123 kg, the carrying capacity of a single bore at a depth of 11.20 meters (Qult) = 596.05 tons, the carrying capacity of a single foundation press permit at a depth of 15 m (Qijin) = 36,304.47 kg / 36.3 tons, the carrying capacity of a single foundation tensile permit at a depth of 15 m (Qijin) = 35,286.2 kg / 35.3 tons, the efficiency of the bore pile group with 2 poles is 0.98, The results of the calculation of the bearing capacity of the pile group (Qg) based on the efficiency of Tower 11 = 36.2 tons. For the stability of the foundation obtained compressive load (bore pile) 40.60 tons, lifting load (Uplift) due to the pull of the conductor = 31, 18 tons, the results of calculation of reinforcement of pile cap / Pad are: For reinforcement of X and Y direction: flexural reinforcement used D16 - 150 mm, and shear reinforcement used D16 - 145 mm, and reinforcement of bore pile using reinforcement D12-50 mm for one pole diameter of 600 mm